Biliary Multifocal Chromosomal Polysomy and Cholangiocarcinoma in Primary Sclerosing Cholangitis. (February 2015) - Eaton, John E; Fritcher, Emily G Barr; Gores, Gregory J; Atkinson, Elizabeth J; Tabibian, James H; Topazian, Mark D; Gossard, Andrea A; Halling, Kevin C; Kipp, Benjamin R; Lazaridis, Konstantinos N
Abstract : Objectives: Polysomy detected by fluorescence in situ hybridization (FISH) is associated with cholangiocarcinoma (CCA) in patients with primary sclerosing cholangitis (PSC). However, a subset of PSC patients with polysomy do not manifest CCA even after long‐term follow‐up. It is unknown if patients with chromosomal gains detected by FISH in multiple areas of the biliary tree (i.e., multifocal polysomy, MFP) are more likely to be diagnosed with CCA than patients with unifocal polysomy (UFP). Therefore, our aim is to determine whether patients with MFP are more likely to manifest CCA compared with patients with other chromosomal abnormalities including UFP and other FISH subtypes. Methods: We performed a retrospective review of PSC patients without a mass lesion who underwent FISH testing at our institution from 1 January 2005 to 1 July 2013. Results: Three‐hundred and seventy‐one PSC patients were included. Compared with patients with UFP, those with MFP were more likely to have weight loss (32 vs. 9%), suspicious cytology (45 vs. 13%) and develop serial polysomy (91 vs. 35%). MFP was associated with CCA (hazard ratio (HR), 82.42; 95% confidence interval (CI), 24.50–277.31) and was the strongest predictor of cancer diagnosis. Suspicious cytology (HR, 26.31; 95% CI, 8.63–80.24) and UFP (HR, 13.27; 95% CI, 3.32–53.08) were also predictive of CCA. MFP, UFP and suspicious cytology remained associated with CCA in the multivariable model. Conclusions: Compared with other FISH subtypes, MFP is the strongest predictor of CCA. However, patients with UFP and suspicious cytology (regardless of FISH status) are also at an increased risk for CCA.